Experimental assessment of confined masonry walls retrofitted with SRG under lateral cyclic loads - Yacilaa, Jhair (2019)
Around the world, many informal masonry buildings have collapsed due to the failure of their bearing walls under lateral seismic loads. This is related to the many involved factors, such the quality of the materials, the quality of workmanship, the lack of technical intervention, and the high seismicity of the zone, among others. However, the fact is that these constructions need to be retrofitted in order to upgrade their ultimate strength and allow them to properly absorb inelastic deformations. Currently, fiber reinforced polymer (FRP) has been widely studied as a retrofitting technique. However, it has some technical and economic disadvantages that are remedied by fiber reinforced mortar (FRM). In this paper, a variant of FRM known as steel reinforced grout (SRG) is studied as a seismic retrofitting technique for cracked confined masonry walls (CMW). For this purpose, three full-scale cracked walls were repaired, retrofitted with SRG strips, and tested under in-plane cyclic loads at the Pontifical Catholic University of Peru (PUCP). The experimental results show the benefits of SRG in improving the lateral displacement ductility, energy dissipation, and stiffness degradation of CMWs.